Quantification of Degradation Products Formed during Heat Sterilization of Glucose Solutions by LC-MS/MS: Impact of Autoclaving Temperature and Duration on Degradation - Sarah Leitzen (MDPI AG, 2021)
Heat sterilization of glucose solutions can lead to the formation of various glucose degradation products (GDPs) due to oxidation, hydrolysis, and dehydration. GDPs can have toxic effects after parenteral administration due to their high reactivity. In this study, the application of the F0 concept to modify specific time/temperature models during heat sterilization and their influence on the formation of GDPs in parenteral glucose solutions was investigated using high-performance liquid chromatography-tandem mass spectrometry (LC-MS/MS). Glucose solutions (10%, w/v) were autoclaved at 111 °C, 116 °C, and 121 °C for different durations. The GDPs glyoxal, methylglyoxal, glucosone, 3-deoxyglucosone/3-deoxygalactosone, 3,4-dideoxyglucosone-3-ene, and 5-hydroxymethylfurfural were quantified after derivatization with o-phenylenediamine by an optimized LC-MS/MS method. For all GDPs, the limit of detection was <0.078 μg/mL, and the limit of quantification was <0.236 μg/mL. The autoclaving time of 121 °C and 15 min resulted in the lowest levels of 3-DG/3-DGal and 5-HMF, but in the highest levels of GO and 2-KDG. The proposed LC-MS/MS method is rapid and sensitive. So far, only 5-HMF concentrations are limited by the regulatory authorities. Our results suggest reconsidering the impurity limits of various GDPs, especially the more toxic ones such as GO and MGO, by the Pharmacopoeias.